Al-Bareedi, Abdullah. “Critical Reviews of Neurolinguistic Programming (NLP): Critique of the Philosophical, Methodological, Associational, and Psychological Foundations,” Year 12, Issue 48 (Spring 1428 AH/ 2007 CE), Pp. 133-166. - البريدي عبدالله (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2007)
Abdullah al-Bareedi’s article discusses the epistemological, cultural, and psychological foundations of Neurolinguistic programming (NLP) in our cultural framework and according to Islamic thought and its principles. It utilizes the critical analytical method by analyzing and critiquing programming in terms of philosophical and cultural vantages and its cultural and psychological implications. The article’s tripartite division offers: 1) a definition of programming in terms of its history, foundations, and principles, and its spread and effectiveness; 2) a critical reading of the foundations of programming; and 3) methodological and cultural examples with Arab programmers. It concludes with a call to Arab and Muslim NLP programmers to develop a project in accordance with the Islamic civilizational makeup.